Arabidopsis immune responses triggered by cellulose‐ and mixed‐linked glucan‐derived oligosaccharides require a group of leucine‐rich repeat malectin receptor kinases. (31st January 2023) - Martín‐Dacal, Marina; Fernández‐Calvo, Patricia; Jiménez‐Sandoval, Pedro; López, Gemma; Garrido‐Arandía, María; Rebaque, Diego; del Hierro, Irene; Berlanga, Diego José; Torres, Miguel Ángel; Kumar, Varun; Mélida, Hugo; Pacios, Luis F.; et al.
SUMMARY: The plant immune system perceives a diversity of carbohydrate ligands from plant and microbial cell walls through the extracellular ectodomains (ECDs) of pattern recognition receptors (PRRs), which activate pattern‐triggered immunity (PTI). Among these ligands are oligosaccharides derived from mixed‐linked β‐1, 3/β‐1, 4‐glucans (MLGs; e.g. β‐1, 4‐D‐(Glc)2 ‐β‐1, 3‐D‐Glc, MLG43) and cellulose (e.g. β‐1, 4‐D‐(Glc)3, CEL3). The mechanisms behind carbohydrate perception in plants are poorly characterized except for fungal chitin oligosaccharides (e.g. β‐1, 4‐d ‐(GlcNAc)6, CHI6), which involve several receptor kinase proteins (RKs) with LysM‐ECDs. Here, we describe the isolation and characterization of Arabidopsis thaliana mutants impaired in glycan perception ( igp ) that are defective in PTI activation mediated by MLG43 and CEL3, but not by CHI6. igp1–igp4 are altered in three RKs – AT1G56145 (IGP1), AT1G56130 (IGP2/IGP3) and AT1G56140 (IGP4) – with leucine‐rich‐repeat (LRR) and malectin (MAL) domains in their ECDs. igp1 harbors point mutation E906K and igp2 and igp3 harbor point mutation G773E in their kinase domains, whereas igp4 is a T‐DNA insertional loss‐of‐function mutant. Notably, isothermal titration calorimetry (ITC) assays with purified ECD‐RKs of IGP1 and IGP3 showed that IGP1 binds with high affinity to CEL3 (with dissociation constant K D = 1.19 ± 0.03 μm ) and cellopentaose ( K D = 1.40 ± 0.01 μM), but not to MLG43, supporting its function as a plant PRR for cellulose‐derived oligosaccharides. Our data suggest that these LRR‐MAL RKs are components of a recognition mechanism for both cellulose‐ and MLG‐derived oligosaccharide perception and downstream PTI activation in Arabidopsis. Significance Statement: The mechanisms of perception of newly described cell‐wall derived oligosaccharides that trigger plant immunity are poorly characterized. Here we described three Arabidopsis thaliana receptor kinases (RK) with Leucine Rich Repeat (LRR) and Malectin (MAL) domains in their ectodomains (ECDs), which are components of a novel mechanism of both cellulose and mixed‐linked β‐glucan (MLGs)‐derived oligosaccharides perception and downstream immune activation. One of these RKs binds cellulose oligosaccharides indicating that is a plant pattern recognition receptor (PRR).